معوقات استخدام التعليم الإلكتروني من وجهة نظر أعضاء هيئة التدريس بجامعة مصراتة في ظل انتشار جائحة كورونا - ساسي، آمنة سليمان محمود; الترهوني، صالحة علي رمضان (المؤسسة العلمية للعلوم التربوية والتكنولوجية والتربية الخاصة, 2023)
هدف البحث إلى معرفة معوقات استخدام التعليم الإلكتروني من وجهة نظر أعضاء هيئة التدريس بكلية التربية جامعة مصراتة في ظل انتشار جائحة كورونا تبعاً لمتغيري الجنس والمؤهل العلمي، وتوصلت نتائج البحث في: 1- وجود فروق دلالة إحصائية عند مستوى دلالة (0.05) بين متوسط آراء العينة حول معوقات استخدام التعليم الإلكتروني تعزى لمتغير الجنس لصالح الإناث. ۲- عدم وجود فروق دلالة إحصائية عند مستوى دلالة (0.05) بين متوسط آراء العينة، حول معوقات استخدام التعليم الإلكتروني تعزى لمتغير المؤهل العلمي (ماجستير - دكتوراه). The aim of the research is to know the obstacles to the use of e-learning from the viewpoint of the faculty members at the Faculty of Education, Misurata University, in light of the spread of the Corona pandemic, according to the variables of gender and academic qualification. “t” test, Pearson correlation coefficient and arithmetic averages. search in: 1_ There are statistically significant differences at the significance level (0.05) between the average sample opinions, about the obstacles to using e learning due to the gender variable in favor of females. 2_ There are no statistically significant differences at the level of significance (0.05) between the average opinions of the sample, about the obstacles to using e- learning due to the educational qualification variable (Masters- PhD).
Keywords: التعليم الإلكتروني -- أعضاء هيئة التدريس -- جائحة كورونا "فيروس كورونا" -- المشكلات التعليمية